Adverse Drug Reaction of Angiotensin Receptor Blockers (Valsartan, Candesartan, Losartan): a Systematic Review - Nurviana, Destawesty; Destiani, Dika P. (Universitas Padjadjaran, Indonesia, 2024)
Hypertension is a significant global health problem, with a growing prevalence worldwide. The most commonly documented ADRs of hypertension medication in primary care records include those associated with angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs). The purpose of this paper is to review and evaluate the potential adverse drug reactions (ADRs) associated with the use of Angiotensin Receptor Blockers (ARBs), specifically valsartan, candesartan, and losartan in the management of hypertension and related diseases. We conducted a systematic review of randomized controlled trial articles that involved valsartan, candesartan, and losartan monotherapy compared with placebo or other standard antihypertensive drugs. PubMed and Google Scholar databases were used in the search for articles in May 2024 and 21 articles were included in this review. This study comprised 21 randomized controlled trials. The study participants' ages ranged from 34.4 years to 76 years. Sample sizes ranged from 16 to 1381 patients with a total 4606 patients. A total of 44 ADRs were observed and the most likely ADRs were headache, dizziness, hypotension, hyperkalemia, nausea, upper respiratory tract infection, and fatigue. Generally, the ADRs that occurred were not fatal and did not lead to discontinuation of therapy. The safety and tolerability profiles of ARBs are among the best for antihypertensive drugs, then overall, the comparison of ARB agents between valsartan, candesartan, and losartan in this class is similar. The most frequent adverse events in the group receiving therapy include headache, dizziness, hypotension, hyperkalemia, nausea, nasopharyngitis, and fatigue.